High-dimensional manifold topology : (World Scientific, 2003)
Proceedings from a conference on recent developments in manifold topology and related areas of geometry, K-theory, and operator algebras. Conference was held June 4-8, 2001 at the Abdus Salam International Centre for Theoretical Physics.